Video Library of Objective Verified Simulated Chest Compression Performances (CIRRUS Research Program Materials) - Rakan S. Al-Rasheed; Jeffrey Devine; Jennifer Dunbar-Viveiros; Mark Jones; Max Dannecker; Gregory Jay; Leo Kobayashi (Association of American Medical Colleges, 2013)
Abstract Introduction CPR Instructor-Coordinator (CPRIC) adherence to published guidelines during resuscitation and learner assessment for basic life support CPR skills has not been experimentally studied. These videos can be used by educators, researchers, and health care institutions as a calibrating "gold standard" to educate CPR learners and CPRICs in chest-compression performance. It may also be used to assist CPRICs in the assessment of proper chest-compression technique. Methods This module is a video library of 12 videos that have been objectively validated to portray adequate chest compressions (six videos) and inadequate compressions (six videos). The videos were scripted and recorded with specific, designated chest-compression parameters encompassing a range of hand positions, rates, depths, and chest releases in combinations that proportionately reflect typical learner cohort performances. The videos may be viewed individually, but videos of adequate and inadequate compressions are placed side-by-side for comparison in a series of PowerPoint presentations. Results This resource was evaluated with a randomized experimental design involving 30 CPRICs. As proof of concept and of utility, analysis of study data revealed the widespread prevalence at baseline of: (1) suboptimal CPRIC subject CPR chest-compression skills (i.e., inadequate hand position, compression depth, chest release/decompression, and overall performance [total correct compressions delivered during simulated CPR session]) and (2) suboptimal CPRIC assessment skills (i.e., pervasively poor accuracy relative to objective parameter specifications during review of the CIRRUS videos). In addition, All CPRIC subjects compressed suboptimally at baseline but real-time feedback improved the proportion of subjects with >77% correct compressions to 0.53 (p < 0.01). Discussion CPRIC adherence to published guidelines during resuscitation and learner assessment for basic life support CPR skills had not been experimentally studied. This resource provides real-time compression feedback which may improve CPR chest-compression skills.